Complete resection of a primitive neuroectodermal tumour arising in the bladder of a 31-year-old female after neoadjuvant chemotherapy - Lam, Cameron J.; Shayegan, Bobby (Canadian Urological Association Journal, 2016)
Primitive neuroectodermal tumours (PNET) that arise in the urinary bladder are an extremely rare occurrence. Very few cases have been reported so far in the literature1-13 and we report another case here in a 31-year-old-female. The patient presented with polyuria, gross hematuria, followed by development of anuria, and was discovered to have a 9.4 cm mass arising in the posterolateral aspect of the bladder. Histologically, the tumour showed small, round, blue cells. Further analysis using break-apart fluorescent in situ hybridization (FISH) revealed non-random chromosomal translocations of the ews gene suggestive of Ewing sarcoma (ES)/ PNET. The patient completed seven cycles of neoadjuvant chemotherapy, which significantly reduced the size of the lesion. Due to the location of the lesion, surgical resection of the entire bladder and urethra with use of a continent cutaneous reservoir was performed. Here, the management of a 31-year-old female with ES/ PNET arising from the bladder is reported.